NanoCarbon 2011 Selected works from the Brazilian Carbon Meeting - Avellaneda, César; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg : Imprint: Springer, 2013)
This book presents highlighted results coming up from NanoCarbon2011, a Brazilian Carbon event. The topics cover the latest advances in Brazilian basic and applied research related to different carbon materials. The chapters address reviews on their fundamental and outstanding properties and describe various classes of new promising high-tech applications for carbon materials.
Preface -- Review of Field Emission from Carbon Nanotubes: Highlighting measuring energy spread -- Synthesis and characterisation of carbon nanocomposites -- Performance of Ni/MgAl2O4 Catalyst Obtained by a Metal-Chitosan Complex Method in Methane Decomposition Reaction with Production of Carbon Nanotubes -- The use of nanostructures for DNA transfection -- Applications of Carbon Nanotubes in Oncology -- CNTs/TiO2 composites -- Synthesis of vertically aligned carbon nanotubes by CVD Technique: A Review -- Thermoset Three-Component Composite Systems using Carbon nantoubes.
Keywords: Nanotechnology; Optical materials; Electronic materials; Materials science; Nanotechnology; Optical and Electronic Materials; Characterization and Evaluation of Materials